KOMPETENSI MENGAJAR GURU DALAM PEMBELAJARAN IPS: Studi Kasus SMP Negeri 119 Jakarta - Erlangga, Aditya Dovio; Siswono, Eko (Edukasi IPS, 2018)
This study aims to determine the relationship pedagogical professional competence of teachers in the learning process of Social Studies, knowing the attitude and behavior of teachers in teaching Social Studies in school and know the social competence of teachers related to the learning activities of Social Studies. This study used qualitative method in order to get a more in depth data through research informants. Source of the data obtained is by using interviews, observation, and literature. Sources of data in this study came from key informants, there are the head of the SMPN 119 Jakarta, students of SMPN 119 Jakarta and one of the teachers who teach in SMPN 119 Jakarta, while the core informants are two Social Studies teachers in SMPN 119 Jakarta. The results of this study conclude there is a linkage between pedagogical competence with professional competence of Social Studies teachers. Although Social Studies teachers experiencing barriers to the delivery and mastery of the material in the classroom so that teachers have the initiative to learn the material and adapt instructional media (power point) will be presented and add a reference from various sources as well as teachers of Social Studies also uses two-way learning namely the relationship of interaction and communication between teachers and students in order to create active learning. Social Studies teachers applying the attitudes and behaviors of discipline, responsibility, tolerance, mutual help also directly taught by teachers through direct interaction and real actions of the school environment. Social competence of Social Studies teachers in terms of interaction and communication that teachers of Social Studies taking place with fellow teachers, students and school committee.